Knowing - Unknowing : African Studies at the Crossroads - Schramm, Katharina; Ndlovu-Gatsheni, Sabelo (Brill, 2024)
This book emerges at a time when critical race studies, postcolonial thought, and decolonial theory are under enormous pressure as part of a global conservative backlash. However, this is also an exciting moment, where new horizons of knowledge appear and new epistemic practices (e.g. symmetry, collaboration, undisciplining) gain traction. Through our critical engagements with structural, relational, and personal aspects of knowing and unknowing we work towards a greater multiplicity of knowledges and practices. Calling into question the asymmetrical global economy of knowledge and its uneven division of intellectual labour, our interdisciplinary volume explores what a decolonial horizon could entail for African Studies at the crossroads.
Keywords: African Studies; Decolonisation; post-colonialism; Africa Multiple; Anthropologie; Katharina Schramm; Sabelo Ndlovu-Gatsheni